Relations between Jews and Samaritans in the Persian period - Eybers, I. H. (1966)
Approximately a decade ago H. H. Rowley undertook a re-examination of the questions surrounding the activities of Sanballat and the erection of the Samaritan temple admitting ""at the outset that there is a complex tangle of issues"" involved ""on which certainty may not always be possible"".1) After this remark Rowley proceeded to discuss the question whether there was another Sanballat besides the adversary of Nehemiah. Then three years ago F.M. Cross published information about a number of papyri and bullae which, among other interesting data, brought to light the name of the governor of Samaria in the year 354 B.C. He was Hannaniah the son of Sanballat2) In the light of this recent discovery it seems that the question which Rowley discussed may be reopened.
Keywords: Samaritans; Persian Period; Jews